Markov Regime Switching GARCH Model and Volatility Modeling for Oil Returns - Gunay, Samet (International Journal of Energy Economics and Policy, 2015)
In conjunction with the recent alternative models, a wide literature has been established for volatility modeling in finance theory. In this study, we examine return volatility of Brent oil returns through GARCH, EGARCH, GJR-GARCH and MRS-GARCH models. As a preliminary test concerning the potential regimes, first, we use modified ICSS test in order to examine the existence of breaks in the variance of return series. All volatility models are formed under normal, GED and student-t distributions. According to the AIC and BIC values, MRS-GARCH model outperforms all other alternative models. Another interesting result is the failure of the models that formed under normal distribution. Keywords: Markov Regime Switching GARCH; Oil Volatility; Variance Breaks JEL Classifications: C14; C22; C58; G14